Necrotizing Fasciitis Caused by A Totally Drug Resistant Achromobacter Xylosoxidans Subspecies Xylosoxidans - Veluri, Gayathri; D., Subbarao (International Journal of Medical Research and Review, 2014)
Achromobacter xylosoxidans is an opportunistic environmental pathogen known to cause many serious infections. In recent years, there have been more number of reported cases of drug resistance with this organism. The choice of appropriate antibiotic and appropriate combination therapy are crucial to save lives of patients who contact this organism. We report the Isolation and Identification of a rare emerging pathogen Achromobacter xylosoxidans sub species xylosoxidans resistant to all recommended antibiotics, in a 60 year old woman with Necrotizing fasciitis. The patient did not respond to combination therapy and finally succumbed to septicaemia, shock and death. Our case report suggests the possible emergence of new pan resistant [totally drug resistant) pathogen - A. xylosoxidans.